2021
DOI: 10.3390/microorganisms9112235
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Diversity and Biotechnological Potential of Cultured and Uncultured Coral-Associated Bacteria

Abstract: Coral-associated microbes are crucial for the biology of their hosts, contributing to nutrient cycling, adaptation, mitigation of toxic compounds, and biological control of pathogens. Natural products from coral-associated micro-organisms (CAM) may possess unique traits. Despite this, the use of CAM for biotechnological purposes has not yet been adequately explored. Here, we investigated the production of commercially important enzymes by 37 strains of bacteria isolated from the coral species Mussismilia brazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 145 publications
(166 reference statements)
1
2
0
Order By: Relevance
“…This research showed that coral-associated bacteria with high potential of lipolysis activity were identified as Staphylococcus haemolyticus. This is similar to previous research that showed high lipolytic activity in coral associated bacteria, identified as the Staphylococcus genus [21].…”
Section: Molecular Identification Of the Coral Bacterium Isolate 301011supporting
confidence: 92%
“…This research showed that coral-associated bacteria with high potential of lipolysis activity were identified as Staphylococcus haemolyticus. This is similar to previous research that showed high lipolytic activity in coral associated bacteria, identified as the Staphylococcus genus [21].…”
Section: Molecular Identification Of the Coral Bacterium Isolate 301011supporting
confidence: 92%
“…Thalassospira bacteria were found in association with healthy corals such as Cladocora caespitosa , Millepora alcicornis , and Sinularia sp. ( 57 60 ) and genetic studies have suggested their possible roles in phosphorus and iron cycles ( 57 , 61 ). On the other hand, OTU0012, OTU0036, and OTU0080 best matched Marisediminitalea aggregata (NR_116838.1; 98.97% gene identity), Allosediminivita pacifica (NR_126266.1; 98.63% gene identity), and Sandaracinus amylolyticus (NR_118001.1; 93.15% gene identity), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…capacities for restoration (de Jesus et al, 2015;Berg et al, 2021;Peixoto et al, 2021), biotechnological application (Cross et al, 2019;Modolon et al, 2020;Vilela et al, 2021), and promotion of organismal health and resilience (Sanders et al, 2019;Woodhams et al, 2020;Berg et al, 2021;Peixoto et al, 2021), predominantly from a anthropocentric point of view (Cavicchioli et al, 2019).…”
mentioning
confidence: 99%